Risk of Progression of Nonalbuminuric CKD to End-Stage Kidney Disease in People With Diabetes: The CRIC (Chronic Renal Insufficiency Cohort) Study - Koye, D.; Magliano, D.; Reid, Christopher; Jepson, C.; Feldman, H.; Herman, W.; Shaw, J. (W.B. Saunders Co., 2018)
Background: Reduced glomerular filtration rate (GFR) in the absence of albuminuria is a common manifestation of chronic kidney disease (CKD) in diabetes. However, the frequency with which it progresses to end-stage kidney disease (ESKD) is unknown. Study Design: Multicenter prospective cohort study. Setting & Participants: We included 1,908 participants with diabetes and reduced GFR enrolled in the Chronic Renal Insufficiency Cohort (CRIC) Study in the United States. Predictors: Urinary albumin and protein excretion. Outcomes: Incident ESKD, CKD progression (ESKD or =50% reduction in estimated GFR [eGFR] from baseline), and annual rate of decline in kidney function. Measurements: ESKD was ascertained by self-report and by linkage to the US Renal Data System. We used Cox proportional hazards modeling to estimate the association of albuminuria and proteinuria with incident ESKD or CKD progression and linear mixed-effects models to assess differences in eGFR slopes among those with and without albuminuria. Results: Mean eGFR at baseline was 41.2 mL/min/1.73 m2. Normal or mildly increased 24-hour urinary albumin excretion (<30 mg/d) at baseline was present in 28% of participants, but in only 5% of those progressing to ESKD. For those with baseline normal or mildly increased albuminuria, moderately increased albuminuria (albumin excretion, 30-299 mg/d), and 2 levels of severely increased albuminuria (albumin excretion, 300-999 and =1,000 mg/d): crude rates of ESKD were 7.4, 34.8, 78.7, and 178.7 per 1,000 person-years, respectively; CKD progression rates were 17.0, 61.4, 130.5, and 295.1 per 1,000 person-years, respectively; and annual rates of eGFR decline were -0.17, -1.35, -2.74, and -4.69 mL/min/1.73 m2, respectively. Limitations: We were unable to compare the results with healthy controls. Conclusions: In people with diabetes with reduced eGFRs, the absence of albuminuria or proteinuria is common and carries a much lower risk for ESKD, CKD progression, or rapid decline in eGFR compared with those with albuminuria or proteinuria. The rate of eGFR decline in normoalbuminuric CKD was similar to that reported for the general diabetic population.